The Role of Social Media in Shaping Public Opinion: A Comprehensive Literature Review. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Social media has emerged as a significant force in shaping public opinion, offering a unique platform for information dissemination, political mobilization, and social movement facilitation. This literature review explores the role of social media in forming public opinion, highlighting its distinctive attributes, such as interactivity, immediacy, and user-generated content, which set it apart from traditional media. The review examines the influence of social media on public sentiment, where it has been shown to impact morale and support for government policies. However, the rise of echo chambers and filter bubbles on social media poses challenges, as these phenomena can distort public perception and contribute to polarization.The review also discusses the potential of social media for real-time public opinion monitoring and its implications for policy-making. While social media enhances civic engagement and democratizes information, it also presents risks, such as the spread of misinformation and conspiracy theories. The review emphasizes the need for critical literacy among users to navigate the complexities of social media and mitigate its negative effects. Future trends and implications, including the impact of emerging technologies and evolving user behaviors, are also considered. Overall, this literature review provides a comprehensive overview of the role of social media in shaping public opinion, highlighting both its positive and negative aspects.